Curriculum Analysis in the History of Islamic Culture (SKI) Subject at MAN 1 Cianjur - Leti Latifah; Mulyawan Safwandy Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Curriculum analysis in understanding the history of Islamic civilization is crucial in facing the challenges of the modern era. The material on the Prophet Muhammad's Da'wah Strategy in Mecca in the Islamic Cultural History (SKI) curriculum is an important aspect, including the wisdom of the Prophet's preaching in facing major challenges in Mecca. This research aims to explore the Prophet's preaching strategy in Mecca and analyze the presentation of this material in the SKI curriculum. The research uses descriptive qualitative methods. The research results show that the SKI material at MAN 1 Cianjur covers the period of the life of the Prophet and Islamic civilization. Learning uses a variety of methods, integrates technology, and emphasizes comprehensive evaluation. The basic concept of the Independent Curriculum provides freedom and focuses on strengthening character. History of Islamic Culture (SKI) helps students develop a deep understanding of Islamic history and moral values. The Prophet's missionary strategy in Mecca is presented carefully, emphasizing monotheism, justice, morality and fortitude. The challenges of the Prophet's preaching in Mecca included persuasion, material advances, offers of religious exchange, insults, physical torture, boycotts, and loss of support. Even though he was faced with serious challenges, the Prophet remained steadfast and built a strong foundation for the development of Islam. This research contributes to the development of the Islamic education curriculum, filling knowledge gaps, and formulating solutions to optimize the SKI curriculum. Through in-depth analysis, it is hoped that more effective and relevant teaching methods can be found to inspire today's Muslim generation.